EKSPERIMENTASI MODEL PEMBELAJARAN RECIPROCAL TEACHING (RT) DAN PROBLEM BASED LEARNING (PBL) PADA MATERI PELUANG DITINJAU DARI KREATIVITAS BELAJAR SISWA KELAS XI SMA/MA NEGERIDI KABUPATEN KETAPANG PROVINSI KALIMANTAN BARAT - Rahman Haryadi; Mardiyana Mardiyana; Dewi Retno Sari S (Jurnal Pembelajaran Matematika, 2014)
Abstract: The aims of this study were to investigate:  (1) which learning model produces students’ better mathematics learning achievement, Reciprocal Teaching (RT), Problem-Based Learning (PBL), or conventional learning model; (2) which students’ have better mathematics learning achievement, those with high, medium, or low learning creativity; (3) viewed from learning models, which students’ have better mathematich learning achievement, those with high, medium, or low learning cretivity; (4) viewed from their creativity level, which learning model produces better mathematich learning achievement RT, PBL, or conventional model. This study was a quasi-experimental research with 3x3 factorial designs. The population was the students of XI class, State SMA/MA in Ketapang District, West Kalimantan Province in year academic 2013/2014. The samples were taken through stratified cluster random sampling technique. The entire samples were 312 students comprising 101 students for the first experimental group, 108 students for the second experimental group and 103 students for control group. The data were collected through the mathematical achievement tests and the learning creativity questionnaires. The hypothesis testing employed  unbalanced two ways of ANOVA. The results of the study are as follows. (1)  RT produced students’ better mathematics learning achievement than PBL and conventional models; PBL produced the same mathematical achievement as conventional model. (2) The students with high learning creativity had better mathematics learning achievement than those with medium and low learning creativity; the students with medium creativity had better achievement than those with low creativity. (3) Treated with RT, the students with high creativity learning  had better mathematics learning achievement than those with medium and low creativity; the students with medium creativity had better achievement than those with low creativity; treated with PBL, the students with high, medium, and low learning creativity had the same achievement; treated with conventional model, students with  high  creativity  had the same achievement as those with medium; the students with high creativity had better achievement than those with low creativity; the students with medium creativity had the same achievement as those with low creativity; (4) Viewed from their high learning creativity, students treated with RT had better mathematics learning achievement than those treated with PBL and conventional  model; those treated with PBL had the same achievement as those treated with conventional model. Viewed from their medium learning creativity, students treated with RT had better mathematics learning achievement than those treated with PBL and conventional model; those treated with PBL had the same achievement as those treated with conventional model. Viewed from their low learning creativity, students treated with RT, PBL and conventional had the same  mathematics learning achievement.Keywords: RT, PBL, learning creativity, the mathematical achievement.